Effect of coupled rotational and transverse vibration on the vortex structures around a rectangular cross-section - Emadeldin, M; Rashed, M R; Mohany, A; Shaaban, M (Journal of physics. Conference series, 2025)
Rectangular structures subjected to turbulent flows are subject to vortex shedding, which induces dynamic forces that depend on the flow conditions and structural motion. Structures with rotational and transverse structural modes may be excited by vortex shedding to oscillate, inducing vibration and fatigue problems. This work investigates the coupled torsional and transverse vibration of a rectangular cross-section with an aspect ratio of 4. To illustrate the effect of mode coupling, three cases are considered: rotation only, rotation and transverse vibration with the same natural frequencies, and rotation and transverse vibration with different natural frequencies. Results show that allowing the structure to vibrate with the two modes with the same natural frequency results in higher vibration amplitudes. Flow fields indicate that higher vibration amplitudes are associated with a wider wake, a distinctive vortex shedding pattern, a widespread turbulent field, and a longer vortex reattachment length on the side of the structure.